SPECIFICATION OF A MODEL OF SUSTAINABLE JUSTICE - ; Laura Lizeth Campos-Guido (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Sustainable Justice is minted in work is to relate it to eight factors that the literature identifies as preponderant factor of Local Development. In this sense, the objective of this paper is to model the relationships between the factors with respect to the construct. For this purpose, it was identified carbon as the central problem from which citizen opinion spreads agenda demands for conservation of resources, but at the expense of state regulation. This discrepancy is assumed as a scenario in which the freedoms, opportunities, capabilities, and responsibilities sustain dialogue, debate, and consensus on the public agenda. This paper develops the argument that the Sustainable Justice is a sociopolitical structure that occurs to the exclusion of the market itself, but highly influenced by the issues that are disseminated in the media. In this sense, this paper proposes that the Sustainable Justice is rather observed from the communities and cities suffering the ravages of global warming. This will anticipate scenarios of conflict between authorities and citizens, as well as predict scenarios of discussion, innovation and social entrepreneurship aimed at conservation of nature.